2015
DOI: 10.1007/s00192-015-2848-9
|View full text |Cite
|
Sign up to set email alerts
|

Bladder symptoms and urodynamic observations of patients with endometriosis confirmed by laparoscopy

Abstract: Endometriosis infiltrating the bladder wall is associated with painful bladder symptoms. Dysfunctional voiding suggests an impairment of the inferior hypogastric plexus by posterior DIE. Clinical preoperative evaluation of bladder function should be systematic; urodynamic tests could be of interest in selected patients with DIE. Endometriosis may be a major cause of bladder pain syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…In agreement with recent findings our study highlights the fact that urinary tract symptoms are highly prevalent in patients with deep endometriosis regardless of previous surgery. The aetiology of pelvic organ dysfunction is complex and includes pathophysiology of the pelvic nerves and plexuses.…”
supporting
confidence: 93%
“…In agreement with recent findings our study highlights the fact that urinary tract symptoms are highly prevalent in patients with deep endometriosis regardless of previous surgery. The aetiology of pelvic organ dysfunction is complex and includes pathophysiology of the pelvic nerves and plexuses.…”
supporting
confidence: 93%
“…A woman of reproductive age complaining of pain symptoms (dysmenorrhea, dyspareunia, and nonmenstrual pelvic pain) is at risk of DIE [32][33][34]. Some studies reported that DIE is associated with lower urinary symptoms (LUTS); however, the prevalence of this association is unclear ranging between 2% and 77% [35][36][37]. According to the findings of a recent research, no difference was reported in the rate of urgency, urinary frequency, voiding symptoms and bladder pain between patient with posterior endometriosis plus BE compared with those with posterior endometriosis only [37].…”
Section: Clinical History and Examinationmentioning
confidence: 99%
“…Some studies reported that DIE is associated with lower urinary symptoms (LUTS); however, the prevalence of this association is unclear ranging between 2% and 77% [35][36][37]. According to the findings of a recent research, no difference was reported in the rate of urgency, urinary frequency, voiding symptoms and bladder pain between patient with posterior endometriosis plus BE compared with those with posterior endometriosis only [37]. Dysuria, frequency, bladder pain, and, less commonly, hematuria, urgency, and urinary incontinence are symptoms related to the presence of BE [3,4,18,38,39].…”
Section: Clinical History and Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, preoperative abnormalities in urodynamic examination may exist in as many as 50 to 96% of patients with deep endometriosis by impairment of the IHP in posterior deep infiltrating endometriosis. 14,20 Thus, incomplete resection in those cases with an aim to preserve pelvic nerves and restore function postoperatively may not be the ideal strategy, since disease evolution itself may further impair function in previously preserved nerves.…”
Section: Nerve Sparing In Endometriosis: Pessimism Of the Intellect Omentioning
confidence: 99%